Knowledge gaps on water issues and consumption habits in at-risk Chinese cities - Xiao, Hong (2014)
This research explores awareness of water issues and beverage consumption habits of students at four universities in northern China, the region most at risk for water shortages. While water is treated as a common property resource in China, there are significant demographic differences in attitudes towards state responsibility for water quality and supply, with older respon-dents, urban residents, and women showing more faith in the government. Surveys of 671 university students reveal a disjuncture between their aware-ness of shortages and pollution issues at the national level, and awareness of local conditions. A second disjuncture is apparent in respondents’ views of local water quality and their own beverage consumption habits. Information on environmental degradation, including water pollution and water depletion, are considered internal documents and are not publicly available. Consequently, non-market mechanisms to manage water do not reflect water’s real value. I discuss implications of these issues for the understanding of environmental policy in China.